Christian Education as a Pillar of Religious Moderation in Facing Campus Radicalism - Benyamin Dadi Ratu Mofu; Esti Regina Boiliu; Melkias Manggoa (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The rise of radicalism on university campuses poses a serious challenge to the world of education, particularly in preserving the unity of a pluralistic and tolerant nation. Radicalism targets not only religious institutions but has also infiltrated academic spaces, including among students. Christian Education, grounded in the values of love, forgiveness, and respect for others, holds strategic potential as a pillar in fostering religious moderation amid the tide of extremism. This study aims to examine the role and contribution of Christian Education in shaping moderate mindsets and character among campus youth. The research method used is qualitative-descriptive with a literature study approach, analyzing relevant literature, documents, and studies on Christian education, religious moderation, and campus radicalism. The novelty of this research lies in its emphasis on integrating the teachings of love in Christian faith with the values of religious moderation as a contextual response to radicalism. The findings reveal that a contextual and transformative Christian education approach can strengthen national insight, encourage interfaith dialogue, and foster a spirit of peaceful coexistence. The discussion highlights the importance of curriculum reformulation, character education reinforcement, and collaboration with various parties to create an academic atmosphere free from radical influences. The conclusion of this study is that Christian Education can serve as a strong foundation for promoting religious moderation and countering campus radicalism by forming students' character grounded in love and tolerance in their daily lives.